From family trunks in the rural region of Coração de Maria to the CE-DOHS bank: a collection of letters for research in historical sociolinguistics - Brito, Patrícia Santos de Jesus (2022)
In this text, we present some reflections on the corpus Cartas Marienses, private epistolary documentation, written by rural workers and housewives, throughout the 20th century, in the rural region of Coração de Maria, in the interior of Bahia. The sample available in (BRITO, 2020) meets one of the agendas of the Program for the History of Brazilian Portuguese (PHPB) – the constitution of diachronic corpora – and was constituted within the scope of the project Corpus Eletrônico de DocumentosHistóricos do Sertão, a PHPB partner. The Cartas Marienses, written by individuals who had little access to the grammatical norms disseminated by the schooling process, therefore, little familiar with the written code, present marks of inability in alphabetical writing in several planes. The Corpus underwent a refined methodology of socio-historical contextualization (PETRUCCI, 2003) and philological treatment, which combined Old and New Philology methods, with the availability of semi-diplomatic and modernized editions, in XML language, using eDictor . The sample in question is of great value for the historical-diachronic studies of Brazilian Portuguese (BP) in the scope of Historical Linguistics and, also, of the Social History of Written Culture, since it makes visible an everyday writing. With little degree of monitoring, writing reveals traces of oral marks, the product of unskilled hands, common people, from disadvantaged social classes, who were on the margins of society, but who, in the letters they wrote, also told their story.